Design and performance study of hybrid photocatalytic reactor-PVDF/MWCNT nanocomposite membrane system for treatment of petroleum refinery wastewater - Moslehyani, A. (2015)
This study focuses on the design and performance of a hybrid system consisting of a photocatalytic reactor and a membrane permeation cell. Initially, an ultraviolet lamp was installed in the photocatalytic reactor to decompose the organic pollutants in the presence of 200 ppm titanium-dioxide (TiO2). Individual hydrocarbon pollutants were identified by gas chromatography–mass spectrometry (GC–MS) analysis of wastewater samples. Polyvinylidene fluoride (PVDF)/multi-walled carbon nanotube (MWCNT) nanocomposite membranes were fabricated to enhance the rejection, flux and fouling resistance for full filtration of pollutants from photocatalytic reactor such as decomposed refinery wastewater and TiO2 photocatalyst. The nanocomposite membranes were characterized by Fourier transform infrared (FTIR), scanning electron microscopy (SEM) and atomic force microscopy (AFM). The TiO2 cross-over during permeation was detected by using an atomic adsorption spectrometer, which proved that TiO2 rejection was more than 99% for oxidized MWCNT nanocomposite membranes. Furthermore, GC–MS analysis was concluded over 90% decomposition which occurred by photocatalytic reaction and practically all pollutants were removed by ultrafiltration permeation cell. The nanocomposite membrane with 1.0 wt.% of oxidized MWCNTs incorporated in PVDF matrix was found to be the best nanocomposite membrane among all of the fabricated membranes for the filtration purposes, due to the over 99% rejection and excellent anti-fouling property.